2020
DOI: 10.1103/physrevlett.124.137202
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Imaging of Magnetoacoustic Waves over Millimeter Distances

Abstract: Using hybrid piezoelectric-magnetic systems we have generated large amplitude magnetization waves mediated by magnetoelasticity with up to 25 degrees variation in the magnetization orientation. We present direct imaging and quantification of both standing and propagating acoustomagnetic waves with different wavelengths, over large distances up to several millimeters in a nickel thin film.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…The suggested approach is applicable for the manipulation of propagating magnon polarons. While the ability of surface acoustic waves to carry magnons across extremely long distances has been recently demonstrated in the weak coupling regime [50], the strong magnon-phonon coupling will enrich collective magnon-phonon transport by pronounced nonreciprocity and give access to the manipulation of the polarization of surface acoustic waves [48]. For instance, at certain direction of external magnetic field, the attenuation and propagation velocity are expected to be different for the magnon polarons propagating in opposite directions along the reciprocal lattice vector of the nanograting [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The suggested approach is applicable for the manipulation of propagating magnon polarons. While the ability of surface acoustic waves to carry magnons across extremely long distances has been recently demonstrated in the weak coupling regime [50], the strong magnon-phonon coupling will enrich collective magnon-phonon transport by pronounced nonreciprocity and give access to the manipulation of the polarization of surface acoustic waves [48]. For instance, at certain direction of external magnetic field, the attenuation and propagation velocity are expected to be different for the magnon polarons propagating in opposite directions along the reciprocal lattice vector of the nanograting [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Long-range transfer of angular momentum between two YIG layers separated by a thick substrate 20 is realized by the magnon–phonon coupling 21 . Direct imaging and quantification of both standing and propagating acoustomagnetic waves were presented in hybrid structures consisting of a piezoelectric substrate underneath Ni 22 . This way, magnon–phonon coupling and excitation by a large-area interdigital transducer (IDT) allowed to transport spin information over a macroscopic distance at specific IDT frequencies 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that bulk phonons in the insulator gadolinium gallium garnet (GGG) can couple two YIG magnetic layers over millimeters [11][12][13][14], raising the possibility of using phonon currents to transfer spin information in nonmagnetic insulators. The surface (Rayleigh) acoustic waves (SAWs), known as excellent sources to pump spin waves via acoustic spin pumping [15][16][17][18][19][20][21], can propagate a longer distance with a larger group velocity [22,23] and thus is promising to transport spin information.…”
Section: Introductionmentioning
confidence: 99%